Enhancement of students' critical thinking ability in the algebraic function derivatives application based on student learning styles during online learning - Marzuki, Marzuki; Negara, Habibi Ratu Perwira; Wahyudin, Wahyudin (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Critical Thinking (CT) ability is an essential skill needed in the 21st century. However, this skill is still under-explored by paying attention to the tendency of Learning Styles (LS) students when online learning is carried out. Therefore, this study aims to determine the differences in the improvement of students' CT abilities based on LS tendencies (visual, auditory, and kinesthetic) when online learning is carried out on algebraic function derivative application materials. Consisting of 4 essay questions given twice, before the sample in this study was a collection of CT, and LS ability scores of class XI science students in Langsa City, totaling 26 students. The researchers collected the data using an LS questionnaire of 30 statements and a written test of CT ability after online learning. Both instruments have been validated. The research method is a pre-experimental design with the type of one-group pretest-posttest. The results showed that (1) students had more dominant kinesthetic LS tendencies compared to visual and auditory LS; (2) students with visual LS have criteria for increasing critical thinking skills in the high category, while auditory and kinesthetic LS is in the medium category; (3) there is a significant difference in the acquisition of CT abilities between visual, auditory, and kinesthetic LS, where students with Visual LS outperform students with Auditory and kinesthetic LS; (4) there are differences in the improvement of CT abilities between students with visual, auditory, and kinesthetic styles in online learning. The improvement in CT ability of students with visual LS is greater than that of Auditory and kinesthetic LS.